Struggle for survival and international recognition of Bosnia and Herzegovina - Hadžić, Izet (Historical Thought, 2025)
The author stresses the importance of democratic and state development of Bosnia and Herzegovina and the difficulties it faced in the decisive battle for independence and international recognition. The disintegration of Yugoslavia, the multinational recognition of Bosnia and Herzegovina and aggression against the internationally recognized state represent significant historical events in modern history of Bosnia and Herzegovina. The author emphasizes the importance of democratic, civilized struggle of political leadership and Bosnian patriots. The political leadership was able to ensure the survival and the international recognition of Bosnia and Herzegovina faced with a devastating aggression of Serbia and Montenegro (SRJ) and the irresponsible behavior of the international community.